Keluarga sebagai ecclesia domestica: Fondasi teologis-biblis pengembangan kecerdasan emosional anak dalam pengasuhan kristiani - Gidion; Herman Poroe (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
The crisis of emotional regulation in the contemporary generation demands a reconceptualization of the Christian parenting paradigm. This research examines the concept of ecclesia domestica as a theological foundation for the development of children's emotional intelligence. Through a practical and constructive theological approach, this study synthesizes patristic thought on the family as a